Flexible biological arsenite oxidation utilizing NOx and O2 as alternative electron acceptors. (July 2017) - Wang, Jie; Wan, Junfeng; Wu, Zihao; Li, Hongli; Li, Haisong; Dagot, Christophe; Wang, Yan
Abstract: The feasibility of flexible microbial arsenite (As III ) oxidation coupled with the reduction of different electron acceptors was investigated. The results indicated the acclimated microorganisms could oxidize As III with oxygen, nitrate and nitrite as the alternative electron acceptors. A series of batch tests were conducted to measure the kinetic parameters of As III oxidation and to evaluate the effects of environmental conditions including pH and temperature on the activity of biological As III oxidation dependent on different electron acceptors. Kinetic results showed that oxygen-dependent As III oxidation had the highest oxidation rate (0.59 mg As g −1 VSS min −1 ), followed by nitrate- (0.40 mg As g −1 VSS min −1 ) and nitrite-dependent As III oxidation (0.32 mg As g −1 VSS min −1 ). The kinetic data of aerobic As III oxidation were fitted well with the Monod kinetic model, while the Haldane substrate inhibition model was better applicable to describe the inhibition of anoxic As III oxidation. Both aerobic and anoxic As III oxidation performed the optimal activity at the near neutral pH. Besides, the optimal temperature for oxygen-, nitrate- and nitrite-dependent As III oxidation was 30 ± 1 °C, 40 ± 1 °C and 20 ± 1 °C, respectively. Highlights: Acclimatized AsOB can oxidize As III with O2, NO3 and NO2 as electron acceptors. Kinetic parameters of As III oxidation using various electron acceptors were tested. The optimum pH and temperature for As III oxidation were examined.